Kinetics of Quality Changes in Porang (Amorphophallus oncophyllus) Flour during Storage at Various Temperatures - Diposari, Rossy Pratiwi; Rahayoe, Sri; Susanti, Devi Yuni (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Porang (Amorphophallus oncophyllus) flour is a raw material for producing glucomannan with low moisture content and hygroscopic properties. Proper storage of porang flour is an important strategy needed in production to maintain the quality. Therefore, this study aimed to assess shelf life of porang flour under various temperature conditions using a reaction kinetics model and to characterize the quality of porang flour during storage. Porang flour was packaged in polyethylene plastic bags and stored at a relative humidity (RH) of ± 70% at different temperatures of 15 °C, 20 °C, 25 °C, and 30 °C. Storage duration was 90 days, and the measurements of viscosity, density, and color were taken at 5-day intervals. Meanwhile, measurements of glucomannan and ash content were conducted at 15-day intervals. Kinetics model was used to determine shelf life of porang flour based on viscosity parameters according to commercial standards set by the Chinese government. The statistical results showed that storage temperature significantly affected density and color but had no significant effect on glucomannan and ash content parameters. Kinetics analysis of viscosity and density changes in porang flour followed a first-order reaction, where higher temperatures resulted in larger rate constants. The validation test with Arrhenius equation derived equations for density and viscosity parameters, namely Y= -4128.1x+6.7104 and Y= -4148.4x+8.1565, respectively. Furthermore, the results showed that shelf life of porang flour with an initial viscosity of 19,000 mPa.s under conditions of ±70% RH and storage temperatures of 15 °C, 20 °C, 25 °C, and 30 °C was 28, 21, 18, and 13 days, respectively, for first-grade quality. For second-grade quality at temperatures of 15 °C, 20 °C, 25 °C, and 30 °C, shelf life was 161, 117, 102, and 76 days, respectively.